N coordination chemistry in diluted InGaAs nitride layers - Gabás-Pérez, Mercedes; López-Escalante, María Cruz; Ramos-Barrado, José Ramón; Ściana, Beata; Dawidowski, Wojciech; Radziewicz, Damian; Dłużewski, Piotr (My University, 2015)
GaAsN and InGaAsN semiconductor alloys with a small amount of nitrogen, so called dilute nitrides, constitute a novel compounds family with applications in telecom lasers and very efficient multijunction solar cells. The incorporation of N, which has a much larger electronegativity and smaller atomic size compared to As, induces a strong structural distortion in the InGaAs coordination chemistry, which will also affect the material electronic structure and band-gap. In particular, the nearest-neighbour bonding configuration of the N in InGaAsN has proven its influence on the band-gap. Our ARXPS results demonstrate that a higher growth temperature favour the formation of In-N bonds.
Keywords: Semiconductores; Dilute nitrides; III-V semiconductors; Angle-resolved XPS